Attitudes of Korean and Chinese traditional medical doctors on education of East Asian traditional medicine - Hyun-Ji Lee; Han Chae; Young-Kyu Lim; Young-Kyu Kwon (Integrative Medicine Research)
Background: The traditional medicine (TRM) of Korea and China share the same cultural tradition for thousands of years, and has experienced modernization process with respect to their distinctive social, cultural, and political influences. The purpose of this study was to analyze the attitude of Korean and Chinese TRM doctors on the current situation and future perspectives of the TRM education. Methods: We analyzed the recognition on the current educational system, and needed curriculums from Korean (n = 188) and Chinese (n = 118) TRM doctors. The validity of the structured questionnaire was examined with exploratory factor analysis with varimax rotation and reliability with Cronbach α. The differences between Korean and Chinese TRM doctors were examined with t test. Results: Chinese TRM doctors consider their educational system more positively as for the standardization and professional ethics than the Korean. The Korean and Chinese wanted more emphasis on the education of medical humanities, clinical skills, medical classics, and alternative medicine, although it was more prominent with the Chinese. Conclusion: This study revealed the attitude of Korean and Chinese TRM doctors on their educational system, and discussed the implication of similarities and differences between them. It would provide foundations for the improvement of the TRM educational curriculums.